Keratoconjunctivitis Sicca in Sjögren’s Syndrome - Su, Yutong; Yang, Chengde (The New England journal of medicine, 2020)
A 64-year-old woman presented with ocular pain, photophobia, and a foreign-body sensation in both eyes. Examination showed corneal epithelial erosions on fluorescence staining, and a diagnosis of Sjögren’s syndrome was made.